Evaluation of Nutrient Foramina of the Dry Adult Human Femur Bone of North Indian Population - Ashok Kumar Sing; Rekha Kumari (Academia Anatomica International, 2019)
Introduction: The Femur bone is a highly vascular structure with unique features in its blood supply via numerous foramina located over its different segments, being named as vascular foramina . Among vascular foramina, nutrient foramen is an important one which gives way to the nutrient artery. Aim: To evaluate the nutrient foramina of the dry adult human femur bone of north Indian population. Subjects and Methods: The present study was undertaken using 50 dry adult human Femur bones of North Indian population. The samples were collected from the Anatomy department of the institute. Results: In the present study, among foramina of 50 dry adult human Femora, 31 Femora had single nutrient foramen, 18 had two nutrient foramina and 1 had three nutrient foramina. The medial lip of lineaaspera of Femur depicted the presence of nutrient foramina in majority of bones suggesting the entry zone for nourishment of shaft by perforating arteries. Size of nutrient foramina were ranging from size ? 0.55 mm to size ? 1.27 mm. Direction of nutrient foramina of all the Femora were directed upwards. Conclusion: This study may help orthopaedic surgeons in planning the surgical treatment of fracture of Femur with a possible reduction in post-operative complications. Combined periosteal and medullary blood supply to the bone cortex helps to explain the success of intramedullary reaming of long bone fractures particularly in the weight bearing Femur.